Nuclear DNA Content of Fine Needle Aspirates of Invasive Ductal Carcinomas of the Breast - Sudip Sarker; Allan Spigelman; Marjorie Walker; Dulcie Coleman (Analytical Cellular Pathology)
Patients with aggressive breast cancers benefit from chemotherapy prior to surgery. If the biology of the breast cancers were better characterised pre‐operatively, more patients at risk could be offered chemotherapy. We have assessed nuclear DNA content of fine needle aspirates (FNA) of 103 invasive ductal breast cancers and compared this to tumour size, node status and histological grade. Median follow‐up was 18 months so no prognostic studies were made. Diploid and non‐diploid tumours were distributed equally in node negative and positive patients. However non‐diploidy status increased in line with known prognostic markers of tumour size and histological grade. This suggests that ploidy might contribute to the pre‐operative assessment of prognosis. We conclude that nuclear DNA of breast cancer FNAs may be of value in the pre‐operative biological assessment of breast cancer patients.